Seasonal soil-plant nitrogen dynamics of a cordgrass salt marsh in response to coastal embankments in Eastern China - Qin, Ge; Feng, Hongyu; Zhao, Hui; Xia, Lu; Yang, Wen; Zhao, Yongqiang; Jeelani, Nasreen; An, Shuqing (Frontiers in Marine Science, 2022)
The effects of coastal embankments on nitrogen (N) cycling in the Spartina alterniflora salt marsh have been extensively reported. However, it remains unclear effects of the embankment on the sizes of diverse N subpools in the plant-soil subsystems year-round. This study examined seasonal changes in various N subpools of plant subsystems; soil subsystems [e.g., soil organic N (SON), recalcitrant organic N (RON), labile organic N (LON), dissolved organic N (DON), ammonium N(NH+4 N), and nitrate N(NO3-N)]; N mineralization [e.g., soil net ammonification (RA) and nitrification (RN) rate]; and immobilization [e.g., microbial biomass N (MBN)] in embanked and adjacent S. alterniflora natural salt marshes on the coast of Eastern China. The embankment significantly reduced the litter N storage by 62.7–71.8% over the four seasons and decreased the root N storage by 53.0% during winter. The SON, LON, RON, and N H +4 N concentrations declined significantly by 43.0–60.2%, 35.8–64.8%, 44.9–59.0%, and 20.8–42.2%, respectively, over the four seasons following the embankment construction. Furthermore, the embankment dramatically reduced the DON concentrations by 21.9% in spring, 14.6% in summer, and 10.4% in winter, while notably diminishing the NO3 N concentrations by 33.4% in autumn and 44.9% in winter, and the RA and RN in spring and summer. However, the embankment clearly increased the MBN concentrations during summer and autumn, the NO3 N concentrations in spring, and the RA and RN in winter at different levels. Due to the decreased soil N inputs from plants, the embankment decreased the organic and inorganic N subpools every season to varying degrees, except for the NO3 N concentration in spring. We suggest that the decreased soil salinity following embankment establishment might increase the uptake of ions by microbes, while stimulating the production of MBN. Ultimately, the NO3 N and DON were two vital N sources for S. alterniflora, and plants absorbed N from the soil to promote their biomass, as well as N concentration and storage. This study is conducive toward understanding the mechanisms behind the effects of coastal embankments on the N transfer among various N subpools in the plant and soil systems.